2003
DOI: 10.1186/cc2243
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction Cardiac surgery with cardiopulmonary bypass (CPB) is a recognized trigger of systemic inflammatory response, usually related to postoperative acute lung injury (ALI). As an attempt to dampen inflammatory response, steroids have been perioperatively administered to patients. Macrophage migration inhibitory factor (MIF), a regulator of the endotoxin receptor, is implicated in the pathogenesis of ALI. We have previously detected peak circulating levels of MIF, 6 hours post CPB. Experimental data have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The distribution or density of HLA-D/ DR antigens on endothelial cells might be different from that on lymphocytes/ macrophages. On the other hand, Moares & Stastny have found that endothelial cells carry other allogeneic antigens shared with monocytes but not with B cells (Moares & Stastny 1977, Stastny 1978. It is not known if these antigens do influence the mixed lymphocyte/endothelial cell culture, but if they have the property of stimulating lymphocytes to proliferate, they might be responsible for masking the HLA-D/ DR specificity when restimulating cells primed to lymphocytes with endothelial cells.…”
Section: Lo4mentioning
confidence: 99%
“…The distribution or density of HLA-D/ DR antigens on endothelial cells might be different from that on lymphocytes/ macrophages. On the other hand, Moares & Stastny have found that endothelial cells carry other allogeneic antigens shared with monocytes but not with B cells (Moares & Stastny 1977, Stastny 1978. It is not known if these antigens do influence the mixed lymphocyte/endothelial cell culture, but if they have the property of stimulating lymphocytes to proliferate, they might be responsible for masking the HLA-D/ DR specificity when restimulating cells primed to lymphocytes with endothelial cells.…”
Section: Lo4mentioning
confidence: 99%